Quantitative Assessment of Regional Pulmonary Transit Times in Pulmonary Hypertension. Issue 3 (9th July 2022) - Moore, Jackson E.; Cerne, John W.; Pathrose, Ashitha; Veer, Manik; Sarnari, Roberto; Ragin, Ann; Carr, James C.; Markl, Michael
Abstract : Background: Pulmonary hypertension (PH) contributes to restricted flow through the pulmonary circulation characterized by elevated mean pulmonary artery pressure acquired from invasive right heart catheterization (RHC). MRI may provide a noninvasive alternative for diagnosis and characterization of PH. Purpose: To characterize PH via quantification of regional pulmonary transit times (rPTT). Study Type: Retrospective. Population: A total of 43 patients (58% female); 24 controls (33% female). RHC‐confirmed patients classified as World Health Organization (WHO) subgroups 1–4. Field Strength/Sequence: A 1.5 T/time‐resolved contrast‐enhanced MR Angiography (CE‐MRA). Assessment: CE‐MRA data volumes were combined into a 4D matrix (3D resolution + time). Contrast agent arrival time was defined as the peak in the signal‐intensity curve generated for each voxel. Average arrival times within a vessel region of interest (ROI) were normalized to the main pulmonary artery ROI (t0 ) for eight regions to define rPTT for all subjects. Subgroup analysis included grouping the four arterial and four venous regions. Intraclass correlation analysis completed for reproducibility. Statistical Tests: Analysis of covariance with age as covariate. A priori Student's t ‐tests or Wilcoxon rank‐sum test; α  = 0.05. Results compared to controls unless noted. Significant without listing P value. ICC ran as two‐way absolute agreement model with two observers. Results: PH patients demonstrated elevated rPTT in all vascular regions; average rPTT increase in arterial and venous branches was 0.85 ± 0.15 seconds (47.7%) and 1.0 ± 0.18 seconds (16.9%), respectively. Arterial rPTT was increased for all WHO subgroups; venous regions were elevated for subgroups 2 and 4 (group 1, P  = 0.86; group 3, P  = 0.32). No significant rPTT differences were found between subgroups ( P  = 0.094–0.94). Individual vessel ICC values ranged from 0.58 to 0.97. Data Conclusion: Noninvasive assessment of PH using standard‐of‐care time‐resolved CE‐MRA can detect increased rPTT in PH patients of varying phenotypes compared to controls. Level of Evidence: 1 Technical Efficacy: Stage 3.